Intracholecystic Papillary Neoplasm of Gallbladder: A Rare Case Report with Review of the Literature - Swati Raj; Mamta Gupta; Naveen Thapliyal (Archives of Medicine and Health Sciences)
Intracholecystic papillary neoplasm (ICPN) of the gallbladder is a relatively new concept and a rare neoplasm. ICPNs are found in 0.4% of cholecystectomies. ICPNs are commonly associated with low-to high-grade dysplasia and can be found with invasive foci. To the best of our research, <100 cases (n = 92) are reported worldwide and only 27 cases have been reported in India. We present a case of ICPN with a detailed review of the literature to illuminate the pitfalls of this entity, which is rarely encountered in routine reporting.